Permasalahan guru IPA SMP mengajarkan IPA terpadu berbasis ethnoscience - Sjaeful Anwar; Omay Sumarna; Ali Kusrijadi (Universitas Pendidikan Indonesia, 2024)
With the implementation of the Kurikulum 2006 KTSP, chemistry became part of the science subject that must be taught to junior high school students. In the Kurikulum 2013, the composition of chemistry material in science subjects was further strengthened. Junior high school science teachers are expected to have competencies in the four fields of science, namely Chemistry, Physics, Biology, and Earth and Space Science (IPBA). However, a field survey conducted in the Subang district showed that many science teachers had difficulty teaching science in an integrated manner. This is due to their formal educational backgrounds, most of which come from physics education programs (49 percent) and biology education programs (49 percent), and only a few from chemistry education programs (2 percent). To this day, science is still taught in fragmented ways: chemistry, biology, physics, and IPBA. This causes a mismatch between the implementation and the curriculum demands, which requires science to be taught in an integrated manner. This mismatch is mainly due to the lack of integrated science textbooks. This training program serves as a solution to the scarcity of integrated science teaching materials. The training uses a blended learning system, combining online and face-to-face models. During the face-to-face sessions, participants are given presentations on science integration and the 4STMD-based teaching material development method. Two online meetings are held to guide the progress of teaching material development. The training is conducted for 8 hours per week, totaling 32 hours. The results of this training show that science teachers are highly motivated to develop integrated science teaching materials based on ethnoscience, resulting in several integrated science teaching materials. Abstrak Dengan diberlakukannya kurikulum KTSP tahun 2006, Ilmu kimia menjadi bagian dari mata pelajaran IPA yang harus diajarkan kepada peserta didik SMP. Pada kurikulum 2013, komposisi materi kimia pada mata pelajaran IPA semakin diperkuat. Guru IPA SMP sudah seharusnya memiliki kemampuan di empat bidang IPA, yaitu Kimia, Fisika, Biologi, dan IPBA. Akan tetapi survey lapangan yang dilakukan di wilayah kabupaten Subang menunjukkan bahwa cukup banyak guru IPA mengalami kesulitan mengajarkan IPA secara terpadu. Hal ini disebabkan oleh latar belakang pendidikan formal mereka yang kebanyakan berasal dari program studi pendidikan fisika (49 persen) dan biologi (49 persen), dan hanya sedikit sekali yang berasal dari program studi pendidikan kimia (2 persen). Sampai saat ini IPA diajarkan secara terpisah-pisah antara IPA kimia, IPA biologi, IPA fisika, dan IPA IPBA. Hal ini yang menyebabkan ketidaksesuaian antara impelentasi dan tuntutan kurikulum, dimana IPA harus diajarkan secara terpadu. Ketidaksesuaian ini disebabkan terutama oleh tidak adanya buku ajar IPA yang disajikan dalam bentuk terpadu. Program pembinaan ini merupakan sebuah solusi bagi kelangkaan bahan ajar IPA terpadu. Pembinaan dilakukan dengan sistem blended learning, yang menggabungkan model daring dan tatap muka. Pada tatap muka diberikan paparan mengenai keterpaduan IPA dan metode pengembangan bahan ajar 4STMD. Dua kali pertemuan dilakukan secara daring untuk memberikan pembinaan progress pengembangan bahan ajar. Pelatihan dilakukan 8 jam per minggu, sehingga seluruhnya 32 jam. Hasil dari pembinaan ini menunjukkan bahwa guru-guru IPA sangat termotivasi untuk mengembangkan bahan ajar IPA terpadu berbasis etnosains, sehingga menghasilkan beberapa bahan ajar IPA terpadu Kata Kunci: 4STMD; bahan ajar; etnosains; IPA terpadu